The rotordynamic analysis of the vibration considering the hydro-electric force supported by rolling elements in 500 kW Francis turbine - Kim, Jung-wan; Kwak, Won-il; Choe, Bok-seong; Kim, Hyoung-ho; Suh, Sang-ho; Lee, Yong-bok (KOREAN SOC MECHANICAL ENGINEERS, 2017)
A Francis turbine which is one of the reaction water turbine types is mainly used in the multipurpose dam. The purpose of this research is to explain the vibration characteristics due to the various causes generated in Francis-turbines generator system. The hydrodynamic force was determined to use the fluid dynamics analysis considering the exciting force that is transmitted to the shaft from the runner part. Besides, in the generator parts electromagnetic forces can have a severe influence on the rotor dynamics in some situations. Because, the hydro turbine-generator system supported by various types of bearing, mechanical vibration analysis is also necessary. Based on a real small-scale Francis-turbine generators parameter, several analysis were performed the stability at the operating speed of the rotor such as natural frequency analysis and forced response analysis. Through this analysis, aside from the mechanical factor, electromagnetic and hydrodynamic factors have also been found to affect vibration.
Keywords: ROTOR